A Purely Organic Tricarbanion. Issue 27 (30th May 2018) - Höfler, Denis; Goddard, Richard; Lingnau, Julia B.; Nöthling, Nils; List, Benjamin
Abstract: How many carbanions can an organic molecule accommodate? The formation of purely organic carbanions with multiple charges is challenging as charge stabilization cannot be achieved through metal coordination. Previously, only quaternary ammonium dicarbanion salts had been reported. By using highly electron‐deficient trifluoromethanesulfonyl (triflyl or Tf) groups, the formation of a purely organic tricarbanion has been realized for the first time. Abstract : How many carbanions can an organic molecule accommodate? The formation of purely organic carbanions with multiple charges is challenging as charge stabilization cannot be achieved through metal coordination. Previously, only quaternary ammonium dicarbanion salts had been reported. By using highly electron‐deficient trifluoromethanesulfonyl (Tf) groups, the formation of a purely organic tricarbanion has been realized for the first time.